RSV Infection in Neonatal Mice Induces Pulmonary Eosinophilia Responsible for Asthmatic Reaction - Zhang, Dan; Yang, Jie; Zhao, Yuanhui; Shan, Jinjun; Wang, Lingling; Yang, Guang; He, Susu; Li, Erguang (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) is a leading cause of lower respiratory tract infections in infants and young children. Severe respiratory viral infection in early-life is intimately associated with childhood recurrent wheezing and is a risk factor for asthma later in life. Although eosinophilic airway inflammation is an important trait in asthma of children, the roles of pulmonary eosinophils in the disease have been inadequately understood. Here we show that RSV infection in neonatal mice causes eosinophilia after allergen stimulation. We showed that RSV infection in neonatal mice exacerbated allergic asthma to allergen stimulation that was accompanied with increased detection of eosinophils in the lungs. In addition, we also detected accumulation of ILC2, CD4 T cells and macrophages. Importantly, adoptive transfer of eosinophils from asthmatic mice with early-life RSV infection exacerbated pulmonary pathologies associated with allergic respiratory inflammation in naive mice in response to foreign antigen. The induction of asthmatic symptoms including AHR, tracheal wall thickening, and mucus production became more severe after further stimulation in those mice. The expression of antigen presentation-related molecules like CD80, CD86, and especially MHC II was markedly induced in eosinophils from OVA-stimulated asthmatic mice. The accumulation of CD4+ T cells in the lungs was also significantly increased as a result of adoptive transfer of eosinophils. Importantly, the deterioration of lung pathology caused by adoptive transfer could be effectively attenuated by treatment with indomethacin, a nonsteroidal anti-inflammatory drug. Our findings highlight the significance of eosinophil-mediated pro-inflammatory response in allergic disease associated with early-life infection of the respiratory tract.